A comparison of cardiac structure and function between female powerlifters, fitness‐oriented athletes, and sedentary controls. Issue 10 (5th September 2020) - Radovanović, Dragan; Stoičkov, Viktor; Ignjatović, Aleksandar; Scanlan, Aaron T.; Jakovljević, Vladimir; Stojanović, Emilija
Abstract: Aim: To compare echocardiographic parameters between female powerlifters, fitness‐oriented athletes, and sedentary controls. Methods: A between‐subject, cross‐sectional experimental design was adopted. Echocardiographic parameters were measured in female powerlifters (n = 10; progressive overload 60%–95% of 1 repetition maximum [RM]), fitness‐oriented athletes (n = 10; 50%–70% of 1‐RM), and sedentary control subjects (n = 10). Comparisons were made with Kruskal‐Wallis tests, one‐way analyses of variance, and eta‐squared ( η 2 ) interpreted as small  = 0.01–0.06, moderate  = 0.061‐0.14, and large > 0.14. Results: Large differences ( P  > .05) were observed between resistance‐trained groups and sedentary controls, whereby relative wall thickness (RWT) and left ventricular (LV) index were greater in powerlifters (RWT: 0.40 ± 0.05, η 2  = 0.15; LV index: 95.6 ± 13.6 g/m 2, η 2  = 0.15) and fitness‐oriented athletes (RWT: 0.40 ± 0.05, η 2  = 0.15; LV index: 97.9 ± 14.2 g/m 2, η 2  = 0.20) compared to sedentary controls (RWT: 0.36 ± 0.05; LV index: 85.9 ± 10.3 g/m 2 ). Large differences were observed in intra‐ventricular septal wall thickness (ISWT) and late diastolic velocity (a') between groups, whereby powerlifters exhibited lower a' (8.6 ± 1.2 cm/s) compared to fitness‐oriented athletes (9.9 ± 0.9 cm/s, η 2  = 0.26, P  = .04) and sedentary controls (9.6 ± 0.9 cm/s, η 2  = 0.19, P  > .05), while fitness‐oriented athletes exhibited greater ISWT (10.1 ± 0.7 mm) compared to sedentary controls (9.4 ± 1.0 mm, η 2  = 0.16, P  > .05). Conclusions: Differences in cardiac structure between powerlifters, fitness‐oriented athletes, and sedentary controls suggest specific cardiac remodeling may occur in response to resistance training, without impairment of cardiac function.